Efeito protetivo de um produto comercial a base de sulfato de cálcio (Fert protetor®) em cafeeiro, eucalipto e feijoeiro - Estevez, Rogério Lopes (2018)
The objective of this work was to evaluate the protective effect of a commercial product based on calcium sulfate (Fert Protetor®) in coffee, eucalyptus and common bean crops. The experiments were carried out in the municipalities of Mandaguari, PR for the coffee and bean crops, in Mogi Guaçu, SP, for a eucalyptus crop, using 0%, 4%, 8%, 16% and 32% Fert Protector®. In coffee the Fert Protector® was applied weekly in nursery seedlings from the presence of the second pair of leaves. As the evaluation was carried out during the nursery period and 60 days after transplantation by the non-destructive method, the incidence and relative severity of the aureolated spot, plant height, neck diameter, root volume and post- plan. There is no experiment with eucalyptus for the use of clones IPB22 and IPB26 (Eucalyptus grandis x E. urophylla), in which biweekly applications of Fert Protetor® were carried out for 120 days. As variables analyzed were shoot height, rooting percentage of minicuttings and activity of the enzyme peroxidase. For the bean experiment, Fert Protector® was applied at V3, R5 and R7 stages and the relative severity of wildfire disease, agronomic variables, productivity and phytoalexin phaseolin induction were evaluated. The results for the coffee experiment show that all Fert Protector® packages were efficient without control of the aureolated spot, however, as dosages of 8%, 16% and 32% decreased up to 70% of the severity of the disease (p <0 , 05). All other variables were positively influenced by Fert Protetor® doses. In the eucalyptus experiment, an application of Fert Protetor®, mainly in 16% and 32%, resulted in higher height, neck diameter, minicutting rooting and peroxidase activity for the two clones studied. For the bean experiment, the results showed the use of Fert Protetor® decreased the severity of the disease up to 90%, positively influencing all agronomic variables and improving productivity. The lower dosages of 4% and 8% are not efficient in the induction of phaseolin in the hypocotyls of the bean, however, as dosages of 16% and 32% presented as good inducers, are superior to the positive treatment with acibenzolar-S-methyl , surpassing it by 17% and 21%, respectively, in the synthesis of this phytoalexin. It is concluded that Fert Protetor® application in coffee, eucalyptus and common bean can control diseases and increase agronomic variables, guaranteeing greater productivity, and even activating plant defense mechanisms such as phytoalexin phaseolin in bean and a peroxidase enzyme in eucalyptus.